Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode Rgec Pada PT. Bank Tabungan Negara, Tbk. Periode 2015-2017 - Kawengian, Fina Priskila; Pelleng, Frendy A. O.; Manoppo, Wilfried S. (JURNAL ADMINISTRASI BISNIS, 2019)
This study aimed to analyze the health of a bank, at PT. Bank Tabungan Negara, Tbk. by using the Rgec method. The Rgec method consists of several components, namely Risk Profile, Good Corporate Governance, Earnings, Capital. of these components also have indicators. which will later rank a bank which is ranked in what category, based on calculations through the company's financial statement data. This research uses quantitative descriptive research. The data source used is secondary data with documentation data collection techniques. Based on the results of data analysis, it was concluded that during the 2015-2017 period, (1) Bank BTN risk profile was in a healthy condition with NPL of 1,60%, 1,40% and 1,30% respectively, and LDR of 109,54%, 103,63%, and 104,19%. (2) GCG for the period 2015-2017 is 2 with healthy criteria. (3) Earnings in the 2015-2017 period are in a healthy condition with ROA of 1,47%, 1,55%, and 1,47%, NIM of 3,96%, 3,81%, and 3,57% , BOPO was 78,67%, 77,96% and 77,12%. (4) Capital is in a very healthy condition with a CAR value of 16,96%, 20,33% and 18,86%. (5) Rgec as a whole is in Composite Rating 1 which is very healthy with a value of 85,71%.